THE INFLUENCE OF FINANCIAL RATIO ON FIRM VALUE WITH ISR AS AN INTERVENING VARIABLE - Suprapto, Yandi; Viviani, Viviani (Islamic University of Kalimantan MAB Banjarmasin, 2024)
One of the more attractive investments for investors is sharia investment because this investment can provide profitable results for both parties and considering that 80% of Indonesia's population is Muslim, the sharia market in Indonesia is very large. The aim of this research is to determine the effect of financial ratios on company value with the intervening variable ISR. The sample for this research is companies listed on the JII index for the 2017-2021 period with a final sample of 24 companies out of 26 companies. This research uses panel data regression data analysis methods. The results of this research are that the firm size variable has a significant but negative relationship with ISR disclosure, the profitability variable has a significant positive relationship and leverage has a significant negative relationship with firm value. Apart from that, the profitability and leverage variables do not have a significant relationship with the ISR score and the firm size variable and the ISR disclosure variable do not have a significant relationship with the firm value. for the intervening variable ISR disclosure is not able to mediate the independent variables profitability, firm size and leverage on the dependent variable firm value.